Public-Key Encryption with Efficient Amortized Updates - Chandran, Nishanth; Ostrovsky, Rafail; III, William E. Skeith (Proceedings Security and Cryptography for Networks, 7th International Conference, SCN 2010, Amalfi, Italy, September 13-15, 2010., 2010)
Searching and modifying public-key encrypted data has received a lot of attention in recent literature. In this paper we re-visit this important topic and achieve improved amortized bounds including resolving a prominent open question posed by Boneh et al. [3].